Bio-pharming in Colorado: a guide to issues for making informed choices - Colorado Institute of Public Policy, author (Colorado State University. Libraries, 2004)
Making informed decisions about bio-pharming in Colorado comes down to case-by-case analysis of economic-development benefits and health, environmental and market-related risks. Raising genetically engineered crops for pharmaceuticals and industrial compounds often is called "molecular farming" or "bio-pharming." Scientists have envisioned the technology for 20 years, but application is in its infancy. In summer 2004, the first bio-pharm crop was planted in Colorado. The experimental research crop of 2,000 engineered corn plants puts Colorado at a policy crossroads. This paper addresses these important questions by providing relevant scientific information and frameworks to guide decision-making.
October 2004.
Keywords: Plant biotechnology -- Colorado; Crops -- Genetic engineering -- Colorado; Pharmaceutical biotechnology -- Colorado